Distinct Helper T Cell Type 1 and 2 Responses Associated With Malaria Protection and Risk in RTS, S/AS01E Vaccinees. (13th May 2017) - Moncunill, Gemma; Mpina, Maxmillian; Nhabomba, Augusto J; Aguilar, Ruth; Ayestaran, Aintzane; Sanz, Héctor; Campo, Joseph J; Jairoce, Chenjerai; Barrios, Diana; Dong, Yan; Díez-Padrisa, Núria; Fernandes, José F; et al.
Summary: Vaccine-specific helper T-cell type 1 and 2 responses are associated with increased and decreased odds of clinical malaria, respectively, in children and infants vaccinated with the malaria vaccine RTS, S/AS01E in a phase 3 trial in Africa. Abstract: Background: The RTS, S/AS01E malaria vaccine has moderate efficacy, lower in infants than children. Current efforts to enhance RTS, S/AS01E efficacy would benefit from learning about the vaccine-induced immunity and identifying correlates of malaria protection, which could, for instance, inform the choice of adjuvants. Here, we sought cellular immunity-based correlates of malaria protection and risk associated with RTS, S/AS01E vaccination. Methods: We performed a matched case-control study nested within the multicenter African RTS, S/AS01E phase 3 trial. Children and infant samples from 57 clinical malaria cases (32 RTS, S/25 comparator vaccinees) and 152 controls without malaria (106 RTS, S/46 comparator vaccinees) were analyzed. We measured 30 markers by Luminex following RTS, S/AS01E antigen stimulation of cells 1 month postimmunization. Crude concentrations and ratios of antigen to background control were analyzed. Results: Interleukin (IL) 2 and IL-5 ratios were associated with RTS, S/AS01E vaccination (adjusted P ≤ .01). IL-5 circumsporozoite protein (CSP) ratios, a helper T cell type 2 cytokine, correlated with higher odds of malaria in RTS, S/AS01E vaccinees (odds ratio, 1.17 per 10% increases of CSP ratios; P value adjusted for multiple testing = .03). In multimarker analysis, the helper T cell type 1 (TH 1)–related markers interferon-γ, IL-15, and granulocyte-macrophage colony-stimulating factor protected from subsequent malaria, in contrast to IL-5 and RANTES, which increased the odds of malaria. Conclusions: RTS, S/AS01E-induced IL-5 may be a surrogate of lack of protection, whereas TH 1-related responses may be involved in protective mechanisms. Efforts to develop second-generation vaccine candidates may concentrate on adjuvants that modulate the immune system to support enhanced TH 1 responses and decreased IL-5 responses.